Aspartic Acid in Health and Disease - Holeček, Milan (Nutrients, 2023)
Aspartic acid exists in L- and D-isoforms (L-Asp and D-Asp). Most L-Asp is synthesized by mitochondrial aspartate aminotransferase from oxaloacetate and glutamate acquired by glutamine deamidation, particularly in the liver and tumor cells, and transamination of branched-chain amino acids (BCAAs), particularly in muscles. The main source of D-Asp is the racemization of L-Asp. L-Asp transported via aspartate-glutamate carrier to the cytosol is used in protein and nucleotide synthesis, gluconeogenesis, urea, and purine-nucleotide cycles, and neurotransmission and via the malate-aspartate shuttle maintains NADH delivery to mitochondria and redox balance. L-Asp released from neurons connects with the glutamate-glutamine cycle and ensures glycolysis and ammonia detoxification in astrocytes. D-Asp has a role in brain development and hypothalamus regulation. The hereditary disorders in L-Asp metabolism include citrullinemia, asparagine synthetase deficiency, Canavan disease, and dicarboxylic aminoaciduria. L-Asp plays a role in the pathogenesis of psychiatric and neurologic disorders and alterations in BCAA levels in diabetes and hyperammonemia. Further research is needed to examine the targeting of L-Asp metabolism as a strategy to fight cancer, the use of L-Asp as a dietary supplement, and the risks of increased L-Asp consumption. The role of D-Asp in the brain warrants studies on its therapeutic potential in psychiatric and neurologic disorders.
Keywords: malate–aspartate shuttle; neurotransmission; glutamate–glutamine cycle; aspartate and cell-to-cell interactions; gluconeogenesis; oxaloacetate; purine-nucleotide cycle; urea cycle; aspartame; branched-chain amino acids